EFEKTIVITAS MODEL PEMBELAJARAN CONCEPT ATTAINMENT DAN MIND MAPPING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI IPS SMA NEGERI 2 KARANGANYAR TAHUN AJARAN 2015/2016 - Wahyu Istuningsih; Mintasih Indriayu; Muhammad Sabandi (Department of Economics Education, Universitas Sebelas Maret, 2018)
The purpose of this research is (1) to find a significant difference between the use of concept attainment model and mind mapping model to student learning outcomes, (2) to determine differences in learning outcomes students more effectively between learning by using the concept attainment instructional models with learning by using mind mapping. This type of research is a kind of quasi-experimental research with study design nonequivalent control group pretest-posttest design. Data analysis technique was used the t test. The results of research showed that: (1) the average value of the two groups have different posttest and evidenced by t-test calculation results obtained t calculate 2,003 bigger than t table 1.992 (df 75th with a 5% significance), (2) the calculation of the value of the gain by t-test obtained t calculate 2,182 bigger than t table 1.992 (df 75th with a 5% significance). Conclusions based on the results of the research are the two models used show a significant difference and concept attainment model is more effective than the model of mind mapping to student learning outcomes on economic subjects class XI IPS SMA Negeri 2 Karanganyar school year 2015/2016.